2015
DOI: 10.1371/journal.pone.0120365
|View full text |Cite
|
Sign up to set email alerts
|

COL9A1 Gene Polymorphism Is Associated with Kashin-Beck Disease in a Northwest Chinese Han Population

Abstract: ObjectiveWe sought to determine whether genomic polymorphism in collagen IX genes (COL9A) was associated with Kashin-Beck disease (KBD).MethodsTwenty seven single nucleotide polymorphisms (SNPs) in COL9AI, COL9A2 and COL9A3 were genotyped in 274 KBD cases and 248 healthy controls using the Sequenom MassARRAY system. Associations between the COL9A polymorphism and KBD risk were detected using an unconditional logistic regression model. Linkage disequilibrium (LD) and haplotypes analysis were performed with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
(40 reference statements)
4
23
0
Order By: Relevance
“…Previous studies have investigated the relationship between COL9A1 sequence variations and risk of such conditions, such as Kashin-Beck disease, multiple epiphyseal dysplasia, and osteoarthritis (Snelgrove et al, 2005;Itoh et al, 2006;Shi et al, 2015). Shi et al (2015) performed a study involving 274 Kashin-Beck disease patients and 248 healthy controls, reporting a significant relationship between COL9A1 rs6910140 and risk of this pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated the relationship between COL9A1 sequence variations and risk of such conditions, such as Kashin-Beck disease, multiple epiphyseal dysplasia, and osteoarthritis (Snelgrove et al, 2005;Itoh et al, 2006;Shi et al, 2015). Shi et al (2015) performed a study involving 274 Kashin-Beck disease patients and 248 healthy controls, reporting a significant relationship between COL9A1 rs6910140 and risk of this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al (2015) performed a study involving 274 Kashin-Beck disease patients and 248 healthy controls, reporting a significant relationship between COL9A1 rs6910140 and risk of this pathology. However, other investigations have generated contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lu et al analyzed 10,823 subjects from 1361 families and observed significant familial aggregation of KBD with an estimated heritability of 41.76 % . Previous research has shown that HLA-DRB1 , ABI3BP , GPX1 (Huang et al 2013;Xiong et al 2010), GPX4 ), CO-L9A1 (Shi et al 2015), SEPS1 (Du et al 2015), ITPR2 , CD2AP , and TNF ) genes were associated with KBD. However, the KBD risk explained by identified susceptibility genes is limited.…”
Section: Introductionmentioning
confidence: 96%
“…Recent epidemiological and genetic study results suggest the interaction between environment factors and susceptibility genes might play a role in the KBD (Shi, Zhang, Lv, Wen, & Guo, ). The pathogenesis of KBD remains elusive (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%